Undergraduate versus graduate nursing students: Differences in nutrition, physical activity, and self-reported body mass index. Issue 7 (3rd October 2022) - Graves, Rebecca J.; Williams, Susan G.; Hauff, Caitlyn; Fruh, Sharon M.; Sims, Brook; Hudson, Geoffrey M.; McDermott, Ryon C.; Sittig, Scott; Shaw, Thomas; Campbell, Matt; Barinas, Jennifer L.; Hall, Heather R.
Abstract: Objective This study compared self-reported nutrition, physical activity, and body mass index (BMI) in undergraduate versus graduate nursing students. Participants Respondents included 233 undergraduate and 230 graduate nursing students in a Southeastern public university. Methods The study was an exploratory, descriptive, cross-sectional comparison administered via online questionnaire including self-reported demographics, nutritional intake, physical activity, and BMI. Results Undergraduates reported exercising more than graduate students. Graduate students reported consuming significantly more vegetables than undergraduates; however, more graduate students self-reported BMIs in overweight and obese categories than undergraduates. Conclusions Findings provide a foundational understanding that interventions or educational programs to improve self-care behaviors of nursing students should be tailored depending on the educational level of the students. Educators must establish self-care skills within nursing students at all levels to help them preserve their health in the fast-paced, strenuous, and stressful work of all echelons of nursing upon completion of the educational program.